A Pragmatic Analysis Of Expressive Utterances Found In "Miracles From Heaven" Movie Script - Ayu Pratiwi, Dita, Drs.Sigit Haryanto,M.Hum (2017)
A320130120. A PRAGMATIC ANALYSIS OF EXPRESSIVE UTTERANCES FOUND IN "MIRACLES FROM HEAVEN" MOVIE SCRIPT. Research Paper. School of Teacher Training and Education Faculty, Muhammadiyah University of Surakarta, January, 2017. This research aims to identify the pragmalinguistics forms of expressive utterances and find out the intentions of expressive utterances in Miracles from Heaven movie script. The type of this research is descriptive qualitative. The data of this research are phrases or sentences in the forms English utterance that supported with the occurrences of expressive utterance. Technique of collecting data used the observation and documentation method. Based on the result of data analysis, the writer found 65 data of expressive utterances in Miracles from Heaven movie script. The result shows that there are 3 types of pragmalinguistics forms thanking, 4 types of pragmalinguistics forms congratulating, 3 types of pragmalinguistics forms apologizing, 4 types of pragmalinguistics forms condoling, 3 types of pragmalinguistics forms pleasure and 2 types of pragmalinguistics forms expression of pain. Besides that related with the intention of expressive utterances, the researcher found 8 data or 12.3% of thanking, 11 data or 16,9% of congratulating, 17 data or 26,2% of apologizing, 14 data or 21.5% of condoling, 6 data or 9.2% statement of pleasure and 9 data or 13.5% expression of pain. Keywords: expressive utterances, descriptive qualitative, pragmalinguistics forms, intention of utterance.